ANALISIS PEMANFAATAN RASI BINTANG MASYARAKAT PULAU JAMPEA KECAMATAN PASIMASUNGGU KABUPATEN KEPULAUAN SELAYAR SEBAGAI PENGETAHUAN TRADISIONAL DALAM NAVIGASI DAN PERTANIAN PERSPEKTIF ASTRONOMI - Siska, Siska; Chotban, Cippa (HISABUNA: Jurnal Ilmu Falak, 2026)
ABSTRACT This study explores the interpretation and utilization of constellations by the community of Jampea Island, Selayar Islands Regency, as traditional knowledge in the field of astronomy. The research focuses on two main aspects: the community’s understanding of constellations and their application in daily life. This is a field research employing a descriptive qualitative approach from cultural and astronomical perspectives. Data were collected through interviews with local fishermen, farmers, and community members, as well as through literature reviews and documentation. Data analysis involved data reduction, presentation, and conclusion drawing. The findings reveal that the people of Jampea Island possess traditional knowledge of constellations that has been passed down through generations and is applied practically. Five main constellations are commonly recognized: Bintoeng Pattaungang as an indicator of a safe fishing season, Bintoeng Purung-purung for identifying the north direction and the onset of the rainy season, Bintoeng Sapo Salayya for determining the south direction and signaling bad weather, Bintoeng Pikka-Pikka as an indicator of strong winds, and Bintoeng Tallu for identifying the west direction and the planting season. The moon phases are also used to determine the best time for fishing and understanding tidal patterns. Fishermen use constellations for timing, navigation, and weather prediction, while farmers use them to determine planting and harvesting periods. The study highlights the importance of preserving traditional knowledge of constellations as part of local navigation, agriculture, and the development of astronomy rooted in indigenous wisdom.